NETVION. The released of a platform for audiovisual content in the cloud - Álvaro Sánchez Olivares; Guiomar Helena Bermejo Sánchez (Centro de Estudios Financieros, 2015)
The next project tries to test those elements that participate in the early phase of the launch of an audiovisual platform in Spain based on cloud computing, in order to confirm that a business opportunity exists in this area. To that purpose, it has been established a theoretical approach to this technology, and also to the perceived trends in the audiovisual contents distribution. To create an own business model, a study of the existing competition has been carried out, focusing in the analysis of companies as Nubeox, Wuaki, Filmin and Yomvi; in this way, relevant gaps have been detected to design a proper offer, and start with the virtualization and social media strategy. The main conclusions have been: lack of flexibility in establishing a business model because of the dominance of the majors, prevalence in offer areas based on single category (video) and establish an own model based on differentiation that includes variety of multimedia contents, maximum compatibility, including the cloud gaming category and a combination of financing forms.